2016
DOI: 10.1016/j.jpag.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Internet Addiction in Hong Kong: Prevalence, Change, and Correlates

Abstract: The results suggest that promotion of positive youth development is a promising direction for preventing Internet addiction in Hong Kong adolescents. Gender and family economic disadvantage must be considered in design of the related prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
100
1
17

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 54 publications
10
100
1
17
Order By: Relevance
“…In Hong Kong, several health-related risk behaviors among adolescents have been identified, including adolescent substance abuse, youth delinquency, mental health problems (e.g., stress and suicidal ideation), internet addiction, school bullying, adolescent sexuality as well as material orientation issues (Chan and Wong 2015; Family Planning Association of Hong Kong 2017; Hong Kong Federation of Youth Groups 2007; Kwok and Shek 2010;Shek 2006Shek , 2007Shek , 2010Shek and Yu 2016). Positive youth development programs may be a promising strategy for promoting adolescent wellbeing and preventing developmental problems (Catalano et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Hong Kong, several health-related risk behaviors among adolescents have been identified, including adolescent substance abuse, youth delinquency, mental health problems (e.g., stress and suicidal ideation), internet addiction, school bullying, adolescent sexuality as well as material orientation issues (Chan and Wong 2015; Family Planning Association of Hong Kong 2017; Hong Kong Federation of Youth Groups 2007; Kwok and Shek 2010;Shek 2006Shek , 2007Shek , 2010Shek and Yu 2016). Positive youth development programs may be a promising strategy for promoting adolescent wellbeing and preventing developmental problems (Catalano et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effect of gender on internet addiction, various studies have generated inconsistent results. Shek et al conducted a study in high school adolescents of Hong Kong and found that internet addictive behavior was consistently high for male gender 10. Chiu et al conducted a study on internet addiction through smart phones in college students of Taiwan and found that female students were more addicted than male students 11.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies, however, did not report incidence of IA conversion. In a local study, positive youth development negatively predicted IA behaviors and males positively predicted IA behaviors in adolescents after 6 years of follow-up [20]. There has been only one longitudinal study in Hong Kong found [20].…”
Section: Introductionmentioning
confidence: 96%